2018
DOI: 10.1590/1678-7757-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effective anticandidal concentration of denture cleanser tablets on some denture base resins

Abstract: ObjectiveAlthough the effectiveness of chemical cleansing against Candida albicans biofilm has been shown, the effective concentration of denture cleanser tablets has not been studied. The aim of this study was to assess the effect of three denture materials against Candida albicans biofilm and to determine effective concentrations of denture cleanser tablets.Material and methodsThe surface-roughness of Acron-hi™, QC-20™ and Deflex™ (n=45 per resin) resins was standardized by using a profilometer and their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
2
23
0
5
Order By: Relevance
“…The results of the present study was in agreement with recent studies which reported that, thermoplastic denture base material has lesser biofilm development and candidal count as compared to heat cure acrylic resin (58,59) . They explained this might be caused by the porosity of heat-cured acrylic resin, which easily triggers the piling of food debris and microorganisms inside (59) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study was in agreement with recent studies which reported that, thermoplastic denture base material has lesser biofilm development and candidal count as compared to heat cure acrylic resin (58,59) . They explained this might be caused by the porosity of heat-cured acrylic resin, which easily triggers the piling of food debris and microorganisms inside (59) .…”
Section: Discussionsupporting
confidence: 93%
“…The surface irregularities on denture base materials may act as a reservoir of infection and increase the possibility of hosting microorganisms even after the cleaning of dentures. Rough and porous surfaces make easier the penetration of bacterial and fungal cells on the denture base resins (36,58,59,63) .…”
Section: Discussionmentioning
confidence: 99%
“…Polidents are available as commercial products, which can easily provide enough cleansing without causing damage to denture resins. 14 According to the manufacturer’s instructions, 5 min of soaking or overnight soaking can kill most microbes. In the present study, we found that the solution of 20 µg/mL AgBr-NP@CTMAB showed similar antifungal activity to inhibit biofilm formation as Polident.…”
Section: Discussionmentioning
confidence: 99%
“…However, this sanitary method is not sufficient to completely eliminate microbial biofilms. 14 The program of denture cleaning has always been an interesting field to researchers, but there is no ideal method to meet the clinical cleaning requirements.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In addition, the majority of complete denture users have advanced age, physical and mental disabilities, systemic diseases, immunosuppression, and impaired manual dexterity for a proper hygiene, [1][2][3] thus increasing the risk of local problems, such as prosthetic stomatitis, 5,6 and systemic infections due to inhalation and ingestion of microorganisms that detach from the mucosa and the denture base. 7 The methods recommended for biofilm removal from the denture can damage the acrylic resin. 8 A suggested alternative was the addition of biocidal agents to the acrylic resin, such as silver nanoparticles, quaternary ammonium, nanosilicon dioxide, nanotitanium dioxide, 2-tert-butylaminoethyl methacrylate.…”
Section: Introductionmentioning
confidence: 99%